Pemetaan Daerah Genangan Dan Kajian Genangan Banjir Pada Kawasan Komersial Di Kelurahan Rawa Makmur - Meilani Belladona (MAJALAH TEKNIK SIMES, 2017)
Sub-district of Rawa Makmur broadly regional 150 Ha and number of residents 5655 men increasingly grows with existence of country college which located in this district. This thing makes area that is formerly mostly in the form of wetland ( marsh) changes over function to become area is woke up. Purpose of this research is to give image of pond distribution pattern happened so that management system design of disaster applicable to especially flooding as well as know the cause of pond happened causing can be done its(the penanggulangan effort. Primary data collecting in the form of topography gauging, passage dimension and interview. Secondary data in the form of location map, data arranges land use, etc. Transformation arranges land use equal to 30% in 3 last year results the happening of pond every the rains. Pond height ranges from 5 - 50 cm in avenue and reachs 100 m at resident area especially which nearby regulus. Factors causing flooding is low topography, transformation arranges land use from area of marsh becomes area of woke up, ugly drainage and only side and destroyed it sluice in disposal of final_ resulting the happening of reverse flow.